Flexible MOF (Metal Organic Framework) microfiltration membrane as well as preparation method and application thereof
By introducing defective metal organic frame particles into the MOF microfiltration membrane and distributing them on the surface of the polymer nanofiber membrane, the problem of insufficient adsorption capacity of the existing MOF microfiltration membrane is solved, and more efficient contaminant adsorption and stability are achieved.
Patent Information
- Application Number
- CN202510167801.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-17
AI Technical Summary
The existing MOF microfiltration membranes have insufficient contaminant adsorption capacity, and the incompatibility between MOF and polymer matrix leads to non-ideal effects, such as interface voids and particle blockage pores.
A flexible MOF microfiltration membrane is used, which consists of polymer nanofiber membrane and defective metal organic frame particles. The defective metal organic frame particles are distributed on the surface of the polymer nanofiber membrane and are prepared by electrospinning and self-assembly reactions.
The adsorption capacity of pollutants is improved, especially the adsorption amount to phosphate is enhanced by about 50%, while the leaching rate of terephthalic acid is reduced, thereby improving the stability and treatment effect of the microfiltration membrane.
Smart Images

Figure CN119656868A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer composite membranes, and in particular to a flexible MOF microfiltration membrane and a preparation method and application thereof. Background Art
[0002] Microfiltration membrane is a filter membrane with a filtration pore size of 0.1~1μm. It can intercept particulate matter through the physical structure of the membrane and is mainly used in separation, filtration and impurity removal. Microfiltration membranes are often made of organic polymer materials or inorganic materials, mainly through phase inversion, melt stretching, etching, radiation curing, sintering and other methods. In recent years, surface modification of microfiltration membranes has become a means of constructing multifunctional microfiltration membranes, especially porous spun fiber membranes that have achieved extremely high filtration specific surface area and modification sites, which can be used to improve the adsorption and removal efficiency of pollutants and improve the treatment effect of wastewater or waste gas.
[0003] Metal-Organic Frameworks (MOFs) refer to crystalline porous materials with multi-level pores or hole structures that are constructed by linking inorganic metal centers and organic functional groups through covalent bonds or ion-covalent bonds. Due to the uniform pore structure and metal active sites, MOF materials play a vital role in the fields of energy, separation, and catalysis, providing the possibility for surface modification of microfiltration membranes and improving the treatment capacity of wastewater or waste gas. However, most MOF materials are nano-scale crystals, and the incompatibility between MOF and the polymer phases of the microfiltration membrane will lead to non-ideal effects, such as interfacial voids and particle clogging of pores; and, due to the phenomenon of MOF agglomeration caused by strong surface tension and high surface energy, MOF is unevenly dispersed in the polymer matrix. These phenomena make the microfiltration membrane obtained after the surface modification of the microfiltration membrane using MOF limited in its adsorption capacity for pollutants and cannot meet the requirements.
[0004] Therefore, there is a need for a flexible MOF microfiltration membrane with high adsorption capacity for pollutants. Summary of the invention
[0005] The purpose of the present invention is to provide a flexible MOF microfiltration membrane and a preparation method and application thereof. The flexible MOF microfiltration membrane provided by the present invention has excellent adsorption capacity for pollutants.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a flexible MOF microfiltration membrane, comprising a polymer nanofiber membrane and defective metal organic framework particles, wherein the defective metal organic framework particles are distributed on the surface of polymer nanofibers of the polymer nanofiber membrane; the diameter of the polymer nanofibers is 5-800nm; and the particle size of the defective metal organic framework particles is 0.1-200nm.
[0007] Preferably, the material of the polymer nanofibers includes one or more of polypropylene, polysulfone, polyethersulfone, polyvinylidene fluoride, polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylonitrile and sulfonated polyethersulfone.
[0008] Preferably, the metal ions of the defective metal-organic framework particles include one or more of Zr ions, Ce ions, Fe ions, Zn ions, Cu ions, Ni ions, Pt ions and Co ions; the organic ligands of the defective metal-organic framework particles include one or more of terephthalic acid, aminoterephthalic acid, dimethylimidazole, tris-benzoic acid, dimethylbenzimidazole, succinic acid, imidazole, pyridine and piperidine.
[0009] Preferably, the mass content of the metal organic framework particles in the flexible MOF microfiltration membrane is 5-35%.
[0010] The present invention also provides a method for preparing the flexible MOF microfiltration membrane described in the above technical solution, comprising the following steps: (1) mixing any one of MOF raw materials with a polymer solution to obtain a spinning solution, and electrospinning the spinning solution to obtain a polymer nanofiber membrane loaded with metal ions or organic ligands; the MOF raw materials include metal salts and organic ligands; (2) Mixing another solution of the MOF raw material in step (1) with the polymer nanofiber membrane loaded with metal ions or organic ligands obtained in step (1) to carry out a self-assembly reaction to obtain a flexible MOF microfiltration membrane.
[0011] Preferably, the mass percentage of the polymer in the spinning solution in step (1) is 5-20%.
[0012] Preferably, the spinning solution contains a metal salt, and the mass percentage of the metal salt in the spinning solution is 0.1-30%.
[0013] Preferably, the spinning solution contains an organic ligand, and the mass percentage of the organic ligand in the spinning solution is 0.1-30%.
[0014] Preferably, the electrospinning parameters in step (1) include: spinning voltage of 5-30 kV; collector speed of 0-800 rpm; injection rate of 0.5-2 mL / h; and receiving distance of 5-20 cm.
[0015] The present invention also provides the use of the flexible MOF microfiltration membrane described in the above technical solution or the flexible MOF microfiltration membrane prepared by the preparation method described in the above technical solution in water treatment and / or waste gas treatment.
[0016] The present invention provides a flexible MOF microfiltration membrane, comprising a polymer nanofiber membrane and defective metal organic framework particles, wherein the defective metal organic framework particles are distributed on the polymer nanofiber surface of the polymer nanofiber membrane; the diameter of the polymer nanofiber is 5-800nm; and the particle size of the defective metal organic framework particles is 0.1-200nm. In the flexible MOF microfiltration membrane provided by the present invention, the polymer nanofiber membrane composed of polymer nanofibers has a large specific surface area, so that the flexible MOF microfiltration membrane has a larger contact area with pollutants; at the same time, the defective MOF particles are distributed on the nanofiber surface of the polymer nanofiber membrane, which can form more adsorption sites in the polymer nanofiber membrane, which is more conducive to improving the adsorption capacity of pollutants. The results of the embodiment show that the flexible MOF microfiltration membrane provided by the present invention has an increased phosphate adsorption capacity of about 50% compared with MOF particles, and the terephthalic acid leaching rate is reduced from 12.0% to 0.3% during the adsorption process. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a SEM image of the flexible MOF microfiltration membrane prepared in Example 1 of the present invention; Figure 2 The photoluminescence spectra of the flexible MOF microfiltration membrane prepared in Example 1 of the present invention and the UiO-66 prepared in Comparative Example 1; Figure 3 Phosphorus adsorption diagram of water treatment of the flexible MOF microfiltration membrane prepared in Example 1 of the present invention, the UiO-66 prepared in Comparative Example 1, and the microfiltration membrane prepared in Comparative Example 2; Figure 4 The ligand leaching diagram of the flexible MOF microfiltration membrane prepared in Example 1 of the present invention and the UiO-66 prepared in Comparative Example 1; Figure 5 The pH value of the solution after the flexible MOF microfiltration membrane prepared in Example 1 of the present invention and the UiO-66 prepared in Comparative Example 1 adsorbed the phosphorus solution at different material dosages; Figure 6 This is a graph showing the adsorption capacity of heavy metals and organic dyes for water treatment by the flexible MOF microfiltration membrane prepared in Example 1 of the present invention, the UiO-66 prepared in Comparative Example 1, and the commercial ion exchange resin. DETAILED DESCRIPTION
[0018] The present invention provides a flexible MOF microfiltration membrane, comprising a polymer nanofiber membrane and defective metal organic framework particles, wherein the defective metal organic framework particles are distributed on the surface of polymer nanofibers of the polymer nanofiber membrane; the diameter of the polymer nanofibers is 5-800nm; and the particle size of the defective metal organic framework particles is 0.1-200nm.
[0019] In the present invention, the pore size of the flexible MOF microfiltration membrane is preferably 0.1-10 μm, more preferably 0.2-1.0 μm. The pore size of the flexible MOF microfiltration membrane provided by the present invention is within the above range, which is more conducive to pollutants entering the microfiltration membrane and improving the adsorption capacity of pollutants.
[0020] The flexible MOF microfiltration membrane provided by the present invention comprises a polymer nanofiber membrane. The nanofiber membrane in the flexible MOF microfiltration membrane provided by the present invention is a fiber membrane formed by randomly and irregularly arranged polymer nanofibers.
[0021] In the present invention, the diameter of the polymer nanofiber is 5-800 nm, preferably 50-500 nm. The diameter of the polymer nanofiber in the flexible MOF microfiltration membrane provided by the present invention is within the above range, and is a nanoscale fiber with a large specific surface area, which can increase the contact area between the flexible MOF microfiltration membrane and the pollutants and provide more filtration specific surface area.
[0022] In the present invention, the structure of the nanofiber is preferably strip, cylindrical, beaded, ribbon, porous, core-shell, hollow, micro-protrusion, fold or spiral, more preferably strip, cylindrical, beaded, ribbon, porous, core-shell or hollow. The nanofiber in the flexible MOF microfiltration membrane provided by the present invention has the above structure, which can provide a larger filtration specific surface area.
[0023] In the present invention, the material of the polymer nanofiber preferably includes one or more of polypropylene, polysulfone, polyethersulfone, polyvinylidene fluoride, polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylonitrile and sulfonated polyethersulfone, and more preferably one or more of polyacrylonitrile, polyvinyl pyrrolidone and polyvinyl alcohol. The present invention adopts the above polymers, which is more conducive to forming continuous nanofibers with uniform diameter.
[0024] The flexible MOF microfiltration membrane provided by the present invention comprises defective metal organic framework particles. In the present invention, the defective metal organic framework particles have abundant lattice defects, and such lattice defect structure can improve the adsorption capacity of pollutants.
[0025] In the present invention, the defective metal organic framework particles are distributed on the surface of the polymer nanofibers of the polymer nanofiber membrane. In the present invention, the distribution of metal organic framework particles on the surface of the polymer nanofibers can provide continuous molecular channels, which is more conducive to improving the adsorption capacity of the flexible MOF microfiltration membrane for pollutants.
[0026] In the present invention, the defective metal organic framework particles are preferably continuously distributed on the surface of the polymer nanofibers of the polymer nanofiber membrane. The present invention continuously distributes the defective metal organic framework particles on the surface of the polymer nanofibers of the polymer nanofiber membrane, and the continuously distributed defective metal organic framework particles contact each other, so that the pores in the defective metal organic framework particles can form continuous channels in the polymer nanofibers, which is more conducive to the adsorption and storage of pollutants and improves the adsorption effect.
[0027] In the present invention, the particle size of the defective metal organic framework particles is 0.1-200 nm, more preferably 5-100 nm. The present invention controls the particle size of the metal organic framework particles within the above range, which is a nanoscale MOF, and is more conducive to forming continuous particles on the polymer nanofibers.
[0028] In the present invention, the metal ions of the defective metal organic framework particles preferably include one or more of Zr ions, Ce ions, Fe ions, Zn ions, Cu ions, Ni ions, Pt ions and Co ions, and more preferably Zr ions, Ce ions or Fe ions; the organic ligands of the defective metal organic framework particles preferably include one or more of terephthalic acid, aminoterephthalic acid, dimethylimidazole, styrene tris-benzoic acid, dimethylbenzimidazole, succinic acid, imidazole, pyridine and piperidine, and more preferably terephthalic acid, aminoterephthalic acid, dimethylimidazole, styrene tris-benzoic acid or dimethylbenzimidazole. The present invention uses the above metal ions and organic ligands to obtain a metal organic framework.
[0029] In the present invention, the defective metal organic framework particles preferably include UiO-66, ZIF-7, ZIF-8, MIL-53, MIL-101, HKUST-1 or MOF-5, and more preferably UiO-66, ZIF-7 or ZIF-8. The present invention adopts the above metal organic framework particles, which have rich porous structures and large specific surface areas, and are more conducive to improving the adsorption capacity of pollutants.
[0030] In the present invention, the mass content of the metal organic framework particles in the flexible MOF microfiltration membrane is preferably 5-35%, more preferably 10-30%. In the present invention, when the mass content of the defective metal organic framework particles is within the above range, it is more conducive to improving the adsorption capacity of the flexible MOF microfiltration membrane.
[0031] In the present invention, the structure of the flexible MOF microfiltration membrane is preferably a flat membrane, a rolled membrane or a hollow fiber membrane, more preferably a flat membrane. The flexible MOF microfiltration membrane provided by the present invention has the above structure and can be applied to different application environments.
[0032] In the flexible MOF microfiltration membrane provided by the present invention, the polymer nanofiber membrane composed of polymer nanofibers has a larger specific surface area and a larger contact area with pollutants; the metal organic framework particles are distributed on the polymer nanofiber surface of the polymer nanofiber membrane, which can provide continuous molecular channels and is more conducive to the adsorption of pollutants; the defective MOF nanoparticles provide abundant active sites and can improve the adsorption capacity of pollutants.
[0033] The present invention also provides a method for preparing the flexible MOF microfiltration membrane described in the above technical solution, comprising the following steps: (1) mixing any one of MOF raw materials with a polymer solution to obtain a spinning solution, and electrospinning the spinning solution to obtain a polymer nanofiber membrane loaded with metal ions or organic ligands; the MOF raw materials include metal salts and organic ligands; (2) Mixing another solution of the MOF raw material in step (1) with the polymer nanofiber membrane loaded with metal ions or organic ligands obtained in step (1) to carry out a self-assembly reaction to obtain a flexible MOF microfiltration membrane.
[0034] In the present invention, any one of MOF raw materials is mixed with a polymer solution to obtain a spinning solution, and the spinning solution is subjected to electrostatic spinning to obtain a polymer nanofiber membrane loaded with metal ions or organic ligands.
[0035] In the present invention, the MOF raw materials include metal salts and organic ligands.
[0036] In the present invention, the metal salt preferably includes one or more of Zr salt, Ce salt, Fe salt, Zn salt, Cu salt, Ni salt, Pt salt and Co salt, and more preferably one or more of Zr salt, Ce salt, Fe salt and Zn salt. In an embodiment of the present invention, the Zr salt may be zirconium tetrachloride; the Ce salt may be cerium nitrate hexahydrate; the Fe salt may be ferric chloride; the Zn salt may be zinc nitrate hexahydrate; and the Cu salt may be copper nitrate hexahydrate. The present invention utilizes metal salts to provide metals for metal organic framework particles.
[0037] In the present invention, the organic ligand preferably includes one or more of terephthalic acid, aminoterephthalic acid, dimethylimidazole, tris-benzoic acid, dimethylbenzimidazole, succinic acid, imidazole, pyridine and piperidine, and more preferably one or more of terephthalic acid, aminoterephthalic acid and dimethylimidazole.
[0038] In the present invention, different types of metal salts and organic ligands correspond to different metal organic framework particles. In an embodiment of the present invention, the metal salt is a Zr salt, the organic ligand is terephthalic acid, and the corresponding metal-organic framework particles may be UiO-66; the metal salt is a Zn salt, the organic ligand is benzimidazole C7H6N2, and the corresponding metal-organic framework particles may be ZIF-7; the metal salt is a Zn salt, the organic ligand is 2-methylimidazole, and the corresponding metal-organic framework particles may be ZIF-8; the metal salt is a Fe salt or an Al salt, the organic ligand is terephthalic acid, and the corresponding metal-organic framework particles may be MIL-53; the metal salt is a Fe salt or a Cr salt, the organic ligand is terephthalic acid, and the corresponding metal-organic framework particles may be MIL-101; the metal salt is a Cu salt, the organic ligand is 1,3,5-benzenetricarboxylic acid, and the corresponding metal-organic framework particles may be HKUST-1; the metal salt is a Zn salt, the organic ligand is terephthalic acid, and the corresponding metal-organic framework particles may be MOF-5.
[0039] In the present invention, the polymer in the polymer solution preferably includes one or more of polypropylene, polysulfone, polyethersulfone, polyvinylidene fluoride, polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylonitrile and sulfonated polyethersulfone, and more preferably one or more of polyacrylonitrile, polyvinyl pyrrolidone and polyvinyl alcohol. The present invention adopts the above polymers, which is more conducive to forming continuous polymer nanofibers.
[0040] In the present invention, the solvent in the polymer solution is preferably one or more of water, N,N-dimethylformamide, dimethylacetamide, methanol, acetone, ethanol and dimethyl sulfoxide, and more preferably one or more of N,N-dimethylformamide, dimethylacetamide, methanol and acetone. The above solvents used in the present invention have good solubility for metal salts, organic ligands and polymers, and can dissolve the above components and form a spinning solution.
[0041] In the present invention, the mass percentage of the polymer in the spinning solution is preferably 5-20%, more preferably 10-20%. The present invention controls the mass percentage of the polymer within the above range, which is more conducive to obtaining a nanometer-scale polymer nanofiber membrane with excellent mechanical properties.
[0042] In the present invention, the spinning solution contains a metal salt, and the mass percentage of the metal salt in the spinning solution is preferably 0.1-30%, more preferably 1-20%, and further preferably 2-15%. The present invention controls the mass percentage of the metal salt in the spinning solution within the above range, which is more conducive to distributing the metal organic framework particles on the surface of the polymer nanofibers.
[0043] In the present invention, the spinning solution contains organic ligands, and the mass percentage of the organic ligands in the spinning solution is preferably 0.1-30%, more preferably 1-20%, and further preferably 10-15%. The present invention controls the mass percentage of the organic ligands in the spinning solution within the above range, which is more conducive to distributing the metal organic framework particles on the surface of the polymer nanofibers.
[0044] The present invention has no particular limitation on the method of mixing the metal salt or organic ligand with the polymer solution, as long as the metal salt or organic ligand and the polymer are fully dissolved to form a spinning solution.
[0045] In the present invention, the metal salt and the organic ligand are not used at the same time in the spinning solution. In the present invention, the metal salt and the organic ligand are selected in the spinning solution, and the metal salt or the organic ligand can be evenly distributed in the polymer nanofiber membrane.
[0046] In the present invention, the electrospinning method is preferably coaxial spinning, super oriented spinning, melt spinning or wet spinning. The present invention obtains polymer nanofiber membranes with different structures by adopting different electrospinning methods.
[0047] In the present invention, the spinning voltage of the electrospinning is preferably 5-30 kV, more preferably 20-30 kV; the collector speed of the electrospinning is preferably 0-800 rpm, more preferably 300-500 rpm; the injection rate of the electrospinning is preferably 0.5-2 mL / h, more preferably 0.8-1 mL / h; the receiving distance of the electrospinning is preferably 5-20 cm, more preferably 10-20 cm. The present invention controls the parameters of the electrospinning within the above range, which is more conducive to the formation of continuous polymer nanofibers.
[0048] The present invention preferably dries the electrospinning membrane after electrospinning to obtain a polymer nanofiber membrane loaded with metal ions or organic ligands. The present invention has no particular limitation on the drying method, and a conventional drying method can be used to fully dry the polymer nanofiber membrane.
[0049] After obtaining the polymer nanofiber membrane loaded with metal ions or organic ligands, another solution of the MOF raw material of the present invention is mixed with the polymer nanofiber membrane loaded with metal ions or organic ligands to undergo a self-assembly reaction to obtain a flexible MOF microfiltration membrane.
[0050] In the present invention, the other solution of the MOF raw material is preferably a metal salt solution or an organic ligand solution.
[0051] In the present invention, the metal salt in the metal salt solution preferably includes one or more of Zr salts, Ce salts, Fe salts, Zn salts, Cu salts, Ni salts, Pt salts and Co salts, more preferably one or more of Zr salts, Ce salts, Fe salts and Zn salts. In an embodiment of the present invention, the Zr salt may be zirconium tetrachloride.
[0052] In the present invention, the concentration of the metal salt solution is preferably 0.002-0.05 g / mL, more preferably 0.007 g / mL. The present invention controls the concentration of the metal salt solution within the above range, which is more conducive to the full self-assembly reaction.
[0053] In the present invention, the organic ligand in the organic ligand solution preferably includes one or more of terephthalic acid, aminoterephthalic acid, dimethylimidazole, tris-benzoic acid, dimethylbenzimidazole, succinic acid, imidazole, pyridine and piperidine, and more preferably one or more of terephthalic acid, aminoterephthalic acid and dimethylimidazole.
[0054] In the present invention, the concentration of the organic ligand solution is preferably 0.002-0.03 g / mL, more preferably 0.005 g / mL. The present invention controls the concentration of the organic ligand solution within the above range, which is more conducive to the full self-assembly reaction.
[0055] The present invention has no particular limitation on the volume of the metal salt solution or the organic ligand solution, as long as the polymer nanofiber membrane can be completely immersed in the metal salt solution or the organic ligand solution.
[0056] In the present invention, the metal salt solution and the organic ligand solution are not used at the same time. In the present invention, when a metal salt is added to the spinning solution, the organic ligand solution is mixed with the polymer nanofiber membrane; in the present invention, when an organic ligand is added to the spinning solution, the metal salt solution is mixed with the polymer nanofiber membrane. In the present invention, by selecting either a metal salt solution or an organic ligand solution, the metal salt or organic ligand formed in the polymer nanofiber membrane undergoes a self-assembly reaction with the organic ligand solution or the metal salt, and the confined diffusion of the polymer or monomer in the nanofiber in the self-assembly reaction is utilized to form a stable metal organic framework nucleation interface on the surface of the nanofiber, thereby forming stable and defective metal organic framework particles.
[0057] In the present invention, the self-assembly reaction is preferably a hydrothermal method or a room temperature synthesis method.
[0058] In the present invention, the temperature of the hydrothermal method is preferably 100-150°C, more preferably 120°C; the time of the hydrothermal reaction is preferably 24-96h, more preferably 24h. The present invention completes the self-assembly reaction through the hydrothermal reaction to prepare UiO-66, ZIF-7, MIL-53, MIL-101, HKUST-1 or MOF-5.
[0059] In the present invention, the preparation method of ZIF-8 or ZIF-67 is preferably a room temperature method. The present invention has no special limitation on the operation method of the room temperature method, and a conventional room temperature method can be used to obtain ZIF-8 or ZIF-67 with a particle size of 0.1 to 200 nm.
[0060] In the present invention, the self-assembly reaction is preferably one or more growths, and the number of the multiple growths is preferably 1 to 10 times, and more preferably 1 to 5 times. The present invention can control the mass content of metal organic framework particles in the flexible MOF microfiltration membrane to 5 to 35% by performing one or more self-assembly reactions.
[0061] In the present invention, after the self-assembly reaction, washing, exchanging and drying are preferably performed in sequence to obtain a flexible MOF microfiltration membrane.
[0062] In the present invention, the cleaning reagent preferably includes one or more of water, N,N-dimethylformamide, dimethylacetamide, methanol, acetone, ethanol and dimethyl sulfoxide, and more preferably one or more of water, N,N-dimethylformamide, dimethylacetamide, methanol and acetone. The present invention can remove impurities on the surface of the flexible MOF microfiltration membrane by cleaning. The present invention has no special limitation on the cleaning method, as long as the impurities in the flexible MOF microfiltration membrane can be fully removed.
[0063] In the present invention, the exchange reagent preferably includes one or more of water, N,N-dimethylformamide, dimethylacetamide, methanol, acetone, ethanol and dimethyl sulfoxide, and more preferably one or more of water, N,N-dimethylformamide, dimethylacetamide, methanol and acetone. The present invention can remove impurities in the pores of the flexible MOF microfiltration membrane through exchange. In the present invention, the exchange method is preferably to immerse the cleaned microfiltration membrane in the exchange reagent. In the present invention, the number of immersions is preferably 2 times, and the time of each immersion is preferably 6 to 24 hours, and more preferably 12 hours.
[0064] The present invention preferably dries the microfiltration membrane obtained after the exchange to obtain a flexible MOF microfiltration membrane. The present invention has no special restrictions on the drying temperature and time, and conventional drying temperature and time can be used to fully dry the flexible MOF microfiltration membrane.
[0065] The method provided by the present invention is simple to operate. First, metal salts or organic ligands are added to the spinning solution to make the metal salts or organic ligands evenly distributed in the polymer nanofibers of the polymer nanofiber membrane; then, the confined diffusion of the polymer nanofiber membrane in self-assembly is utilized to form a stable MOF nucleation interface on the fiber surface, thereby forming stable and defective metal organic framework particles.
[0066] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0067] Example 1 A flexible MOF microfiltration membrane, the flexible MOF microfiltration membrane is composed of a polymer nanofiber membrane and defective metal organic framework particles, the defective metal organic framework particles are distributed on the surface of polymer nanofibers of the polymer nanofiber membrane; the average diameter of the polymer nanofibers is 360nm; the average particle size of the defective metal organic framework particles is 15.2nm; the mass content of the metal organic framework particles in the flexible MOF microfiltration membrane is 25.6%; The preparation method of the flexible MOF microfiltration membrane is: (1) 0.5 g of terephthalic acid, 0.25 g of polyacrylonitrile and 30 mL of N,N-dimethylformamide were mixed and dissolved to obtain a spinning solution, and the spinning solution was loaded into an electrospinning injector, the applied voltage was 20 kV, the collector speed was 300 rpm, the injection rate was 0.8 mL / h, and after drying, a polymer nanofiber membrane loaded with an organic ligand was obtained; (2) 0.7 g zirconium tetrachloride, 10 mL N,N-dimethylformamide, 30 mL acetone and 10 mL glacial acetic acid were mixed and dissolved to obtain a mixed solution, the polymer nanofiber membrane was immersed in the mixed solution, placed in a hydrothermal reactor, and subjected to hydrothermal reaction at 120 °C for 24 h for self-assembly, and then the obtained microfiltration membrane was washed 3 times with acetone solution and immersed in methanol 2 times, each time for 12 h, and dried to obtain a flexible MOF microfiltration membrane; The specific surface area of the flexible MOF microfiltration membrane prepared in this embodiment is 217.21 m 2 / g.
[0068] Comparative Example 1 A preparation method of UiO-66: (1) Add 0.7 g zirconium tetrachloride into 30 mL N,N-dimethylformamide solution and dissolve to obtain solution A; (2) Add 0.5 g of terephthalic acid into 30 mL of N,N-dimethylformamide solution and dissolve to obtain solution B; (3) Solution A was added dropwise into solution B, and 10 mL of glacial acetic acid was added and stirred to obtain solution C; (4) Add solution C into a hydrothermal reactor and react at 120°C for 24 hours; (5) The obtained particles were washed with N,N-dimethylformamide solution for 3-5 times and immersed in methanol for 2 times, each time for 12 h, to obtain UiO-66.
[0069] Comparative Example 2 A method for preparing a flexible MOF microfiltration membrane is as follows: 0.1 g of UiO-66 prepared in Comparative Example 1 was mixed with 30 mL of N,N-dimethylformamide and 0.25 g of polyacrylonitrile to obtain a mixed solution, and the spinning solution was loaded into an electrospinning injector, the applied voltage was 20 kV, the collector speed was 300 rpm, the injection rate was 0.8 mL / h, and a polymer nanofiber membrane was obtained after drying; the obtained microfiltration membrane was washed 3 times with an acetone solution, and immersed in methanol 2 times, each time for 12 hours, and a flexible MOF microfiltration membrane was obtained after drying; The specific surface area of the flexible MOF microfiltration membrane prepared in this comparative example is 49.73 m 2 / g.
[0070] Application Example 1 The adsorption performance of the flexible MOF microfiltration membrane prepared in Example 1 on the phosphorus-containing solution was tested as follows: 10 mg of the flexible MOF microfiltration membrane prepared in Example 1 was added to a serum bottle containing 100 mL of potassium dihydrogen phosphate solution (phosphorus content 1 mg / L, pH = 6.5) and shaken at 200 r / min for 24 h at 25 ° C to reach adsorption equilibrium. The supernatant was collected at specific times (0 h, 1 h, 2.5 h, 4 h, 6 h, 8 h and 10 h) to determine the residual phosphate concentration, and the pseudo-first-order model was used to characterize the adsorption kinetics.
[0071] Comparative application example 1 The adsorption performance of UiO-66 prepared in Comparative Example 1 on phosphorus-containing solution was tested, and the testing method was the same as that in Application Example 1.
[0072] Comparative Application Example 2 The adsorption performance of the microfiltration membrane prepared in Comparative Example 2 on the phosphorus-containing solution was tested using the same testing method as in Application Example 1.
[0073] Application Example 2 The adsorption test of heavy metals and organic dyes by the flexible MOF microfiltration membrane prepared in Example 1 was conducted as follows: a heavy metal salt solution (heavy metal ions were Cr 3+ 、As 5+ , Sb 5+ 、Cd 2+ and Pb 2+ ) and organic dye (MB) solution, and then 10 mg of the flexible MOF microfiltration membrane prepared in Example 1 was added to a serum bottle containing 100 mL of the above heavy metal salt solution or organic dye solution, and oscillated at 200 r / min at 25 °C for 24 h to reach adsorption equilibrium, and the pseudo-first-order model was used to characterize the adsorption kinetics.
[0074] Comparative Application Example 3 The adsorption performance of the flexible MOF microfiltration membrane prepared in Comparative Example 1 on heavy metals and organic dyes was tested using the same testing method as in Application Example 2.
[0075] Comparative Application Example 4 The adsorption performance of commercial ion exchange resin (D201 polystyrene anion exchange resin) on heavy metals and organic dyes was tested. The test method was the same as that in Application Example 2.
[0076] Test Case (1) The photoluminescence spectra of the flexible MOF microfiltration membrane prepared in Example 1 and the UiO-66 prepared in Comparative Example 1 are shown in Figure 2 As shown. Figure 2 It can be seen that at an excitation wavelength of 280 nm, the intensity of the fluorescence signal λex / λem=280 nm / 395 nm is mediated by the coordination number of Zr-O clusters and BDC in the UiO-66 matrix, and is negatively correlated with the content of defect sites, among which Example 1 has the most abundant defects, indicating that this method has a significant effect on defect formation.
[0077] (2) According to the adsorption performance test method of UiO-66 prepared in Application Example 1 and Comparative Application Example 1 and the microfiltration membrane prepared in Comparative Example 2, the water treatment phosphorus adsorption graphs of the flexible MOF microfiltration membrane prepared in Example 1, the UiO-66 prepared in Comparative Example 1 and the microfiltration membrane prepared in Comparative Example 2 are obtained as shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the adsorption capacity of the flexible MOF microfiltration membrane prepared in Example 1 can reach 66 mg / g, while the adsorption capacity of UiO-66 prepared in Comparative Example 1 is 42 mg / g, and the adsorption capacity of the flexible MOF microfiltration membrane prepared in Example 1 enhances the adsorption of phosphate by about 50%. This is because the flexible MOF microfiltration membrane prepared in the present invention improves the adsorption capacity of pollutants by adsorbing active sites rich in defective MOF on the surface of nanofibers, thereby improving the treatment effect of wastewater.
[0078] (3) The stability test of the flexible MOF microfiltration membrane prepared in Example 1 and the UiO-66 prepared in Comparative Example 1 was performed by adding the samples into serum bottles containing 100 mL of potassium dihydrogen phosphate solution (phosphorus content of 0.5-50 mg / L, pH=6.5) and shaking at 200 r / min for 24 h at 25 °C to achieve adsorption equilibrium. During the adsorption experiment, the solution was extracted to determine the ligand concentration to determine the ligand leaching in UiO-66.
[0079] The ligand leaching diagrams of the flexible MOF microfiltration membrane prepared in Example 1, the UiO-66 prepared in Comparative Example 1, and the microfiltration membrane prepared in Comparative Example 2 are shown in FIG. Figure 4 The corresponding data are shown in Table 1.
[0080] Table 1 Ligand leaching results of different adsorbent materials (%)
[0081] from Figure 4 As can be seen from Table 1, the mass percentage of ligand leaching of UiO-66 prepared in Comparative Example 1 is much higher than that of the flexible MOF microfiltration membrane prepared in Example 1. This is because the method provided by the present invention can stably grow metal organic framework particles on the surface of nanofibers, effectively reduce the ligand leaching of UiO-66, and improve the stability of the flexible MOF microfiltration membrane.
[0082] (4) The flexible MOF microfiltration membrane prepared in Example 1 and the UiO-66 prepared in Comparative Example 1 were respectively placed in a potassium dihydrogen phosphate solution with an initial phosphorus concentration of 1 mg / L. After adsorption equilibrium, the pH value in the solution was observed. Figure 5 And as shown in Table 2.
[0083] Table 2 pH value of water after different adsorbent materials were immersed in water
[0084] from Figure 5 As can be seen from Table 2, under the conditions of different material addition amounts, the initial phosphorus concentration is 1 mg / L, and the pH is measured after adsorption equilibrium. Comparative Example 1 is extremely unstable during the adsorption process, and the leaching of BDC causes the solution to gradually become acidic, while Example 1 shows extremely high stability, and the pH value of the solution remains unchanged.
[0085] (5) The water treatment heavy metal and organic dye adsorption capacity of the flexible MOF microfiltration membrane prepared in Example 1, the UiO-66 prepared in Comparative Example 1, and the commercial ion exchange resin (D201 polystyrene anion exchange resin) obtained by the methods of Application Example 3 and Comparative Application Examples 3-4 are shown in the figure. Figure 6 And as shown in Table 3.
[0086] Table 3 Results of heavy metal and organic dye adsorption capacity of water treatment by different adsorbent materials (mg / g)
[0087] from Figure 6 As can be seen from Table 3, the flexible MOF microfiltration membrane prepared in the present invention exhibits excellent adsorption capacity for both heavy metal ions and organic dyes.
[0088] From the above results, it can be seen that the flexible MOF microfiltration membrane provided by the present invention has excellent adsorption capacity for heavy metal ions and organic dyes. This is because in the flexible MOF microfiltration membrane provided by the present invention, the polymer nanofiber membrane composed of polymer nanofibers has a large specific surface area and a larger contact area with pollutants; at the same time, the metal organic framework particles are distributed on the polymer nanofiber surface of the polymer nanofiber membrane, which can provide continuous molecular channels and is more conducive to the adsorption of pollutants; the present invention adjusts the elementary structure of MOF through a confinement strategy to obtain defective MOF nanoparticles, which provide more abundant active sites and can improve the adsorption capacity for pollutants. This method has broad application prospects in the adsorption and separation of conventional pollutants (such as heavy metals, etc.) and new pollutants (such as perfluorinated compounds, etc.) in water treatment, and in the separation of conventional gases (such as carbon dioxide, methane, etc.) and toxic gases (such as sulfur dioxide, dimethyl methylphosphonate, etc.).
[0089] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A flexible MOF microfiltration membrane, comprising a polymer nanofiber membrane and defective metal organic framework particles, wherein the defective metal organic framework particles are distributed on the surface of polymer nanofibers of the polymer nanofiber membrane; the diameter of the polymer nanofibers is 5 to 800 nm; and the particle size of the defective metal organic framework particles is 0.1 to 200 nm.
2. The flexible MOF microfiltration membrane according to claim 1, characterized in that: The material of the polymer nanofiber includes one or more of polypropylene, polysulfone, polyethersulfone, polyvinylidene fluoride, polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylonitrile and sulfonated polyethersulfone.
3. The flexible MOF microfiltration membrane according to claim 1, characterized in that: The metal ions of the defective metal organic framework particles include one or more of Zr ions, Ce ions, Fe ions, Zn ions, Cu ions, Ni ions, Pt ions and Co ions; the organic ligands of the defective metal organic framework particles include one or more of terephthalic acid, aminoterephthalic acid, dimethylimidazole, tris-benzoic acid, dimethylbenzimidazole, succinic acid, imidazole, pyridine and piperidine.
4. The flexible MOF microfiltration membrane according to claim 1, characterized in that: The mass content of the metal organic framework particles in the flexible MOF microfiltration membrane is 5-35%.
5. The method for preparing the flexible MOF microfiltration membrane according to any one of claims 1 to 4, comprising the following steps: (1) mixing any one of MOF raw materials with a polymer solution to obtain a spinning solution, and electrospinning the spinning solution to obtain a polymer nanofiber membrane loaded with metal ions or organic ligands; the MOF raw materials include metal salts and organic ligands; (2) Mixing another solution of the MOF raw material in step (1) with the polymer nanofiber membrane loaded with metal ions or organic ligands obtained in step (1) to carry out a self-assembly reaction to obtain a flexible MOF microfiltration membrane.
6. The preparation method according to claim 5, characterized in that: The mass percentage of the polymer in the spinning solution in step (1) is 5-20%.
7. The preparation method according to claim 5 or 6, characterized in that: Any one of the metal salt and the organic ligand is a metal salt, and the mass percentage of the metal salt in the spinning solution is 0.1-30%.
8. The preparation method according to claim 5 or 6, characterized in that: Any one of the metal salt and the organic ligand is an organic ligand, and the mass percentage of the organic ligand in the spinning solution is 0.1-30%.
9. The preparation method according to claim 5, characterized in that: The parameters of the electrospinning in step (1) include: a spinning voltage of 5 to 30 kV; a collector speed of 0 to 800 rpm; an injection rate of 0.5 to 2 mL / h; and a receiving distance of 5 to 20 cm.
10. Use of the flexible MOF microfiltration membrane according to any one of claims 1 to 4 or the flexible MOF microfiltration membrane prepared by the preparation method according to any one of claims 5 to 9 in water treatment and / or waste gas treatment.
Citation Information
Patent Citations
Nanofiber-loaded metal organic framework air purification material and preparation method thereof
CN111013271A
Sugarcoated haw-shaped MOFs fiber membrane as well as preparation method and application thereof
CN115000624A
Preparation method and application of bimetal organic framework composite fiber membrane
CN119162734A
Arresting gear
KR1020230135425A
Hardware / software defect detection method using deep learning and analysis apparatus
KR102420514B1
Cited By
MOF-based material with mimic enzyme activity as well as preparation method and application of MOF-based material
CN120289821A